Performance analysis of heat recovery system for a turbofan engine using intercooler and recuperator via Aspen Plus - Chua, I.C.W; Saadon, S. (EDP Sciences, 2024)
Global warming and climate change have been major problems in the present world. Greenhouse gas emissions contribute to global warming in which carbon dioxide being the best known. The aviation sector (excluding aerospace) has contributed to a total of 49.4 billion tons of carbon dioxide emission in 2016 alone. A solution to curb the increase of greenhouse gases has been proposed to temporarily solve this problem while future technological advancements occur. Having a heat recovery system by using heat exchangers in the engine helps to not only improves the performance of the engine but to also reduce temperature of the exhaust gases that will be eliminated as waste heat into the atmosphere. The main objective of the introduction of intercoolers and recuperators is to reduce the thrust specific fuel consumption whilst increasing the thrust and reducing emissions. This research thesis focuses on the analysis of intercooling and recuperation within the aspects of thermodynamics to be integrated into a typical turbofan engine. The analysis will be conducted via process simulation software – Aspen Plus V11 and the data from the software will be exported to Microsoft Excel for post-processing and graph visualization. Three main objectives of the study are to determine whether compression work will be reduced, studying the increase of thrust and performance of the engine with the positioning of heat exchangers and the improvement of TSFC with the integration of heat exchangers. For the first objective, it has been proven that there is a reduction in compression work for the recuperated engine of 7.64% but there is a 13.17% increase in compression work for the intercooled engine. For the second objective, thrust increased in both recuperated and intercooled cycles with 1.14% and 1.31% for the recuperated and intercooled cycles, respectively. Finally for the third objective, a decrease in TSFC for both recuperated and intercooled cycles show that both the heat recovery systems have an improvement of TSFC.